EXPRESSION OF COMPARATIVE RELATION IN LANGUAGE (Scientific journal of the Fergana State University, 2024)
In linguistics, it is important to study language as a complex system, to analyze all language units based on their form and content, and to study their syntactic, semiotic and pragmatic nature and their significance in speech. It is the research of linguistic units that express different relations that has theoretical and practical importance in linguistics, in particular, combining linguistic tools that express comparative relations into one semantic group and highlighting them on the basis of a certain system makes it possible to show the system-structural nature of the language. The main goal of this article is to identify the linguistic units that represent the comparative relationship at different levels, mainly at the syntactic level, and to analyze them on the example of different languages. Methods such as description, classification, comparison, contrast, content and pragmatic analysis were used in the coverage of this article.